Energy Security Strategy for Nepal - Parajuli, Chhabindra (Prashasan: The Nepalese Journal of Public Administration, 2024)
Climate change, food security, and energy security pose new economic challenges. The main causes of energy crises stem from overconsumption, inadequate infrastructure, overpopulation, and high energy demand. Urgent action is needed to prioritize the energy sector as a key development priority. Addressing three critical issues—affordability risks, electricity security, and the resilience of clean energy supply chains-is essential to ensure Energy Security for All (ESfA). All levels of government—federal, provincial, and local-as well as international organizations, must collaborate using robust policy measures to attract new investors to energy sector projects. Additionally, it is crucial to formulate and implement new strategies for energy sector development while enhancing the capacity of public institutions and business service providers involved in the energy sector.